GAYA PENGGUNAAN BAHASA DALAM JUDUL VIDEO DI YOUTUBE: KAJIAN STILISTIKA PRAGMATIK - Hemas Haryas Harja Susetya (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
Youtube is something that is very popular in Indonesia. One thing that affects the video watched by visitors is the title that labels the video. The purpose of this study is to describe the style of language use in the video title so that we can find out the characteristics of the language of the video title on Youtube. This research is a qualitative descriptive study. The data were collected using the observation method with the basic technique of listening and the advanced technique of taking notes. The data in this study are in the form of video titles on Youtube which contain a distinctive style of using language. This study took data from 20 October 2019 to 20 November 2019. What needs to be emphasized is that the data source is only taken in the column "popular weekly videos". The data analysis in this study used the referential equivalent method with the comparative link technique to support codification, reduction, presentation, and interpretation in accordance with the qualitative research framework. The results of this study, the style of language use in video titles on Youtube tends to disclose the assessment. Of the 48 video titles, 34 data on the style of use of assessment disclosure language were found. As for the style of language use by expressing the assessment through calls, there are 15 data from 48 video titles. Followed by 5 language usage style data by expressing the taste of 48 video titles, 5 direct imperative language usage style data from 48 video titles, and 5 indirect imperative language usage style data from 48 video titles. Keywords: language usage style, video title, Youtube, pragmatic stylistics